The Uses and evaluation of water resources in the Zalm river basin - Abdulrahim Azeez, Tahseen; Hamasalh Sharazory, Mohmeed (Zanco Journal of Human Sciences, 2022)
This study deals with the subject of a geographical assessment of the use of water resources in the Zalam River Basin. The aim of this study is to highlight the reality of the current uses of water resources for various purposes in the study area. And to achieve a balance between the volume of incoming, surface and underground water in the study area, and to find the amount of consumption of water by the population in the various activities. It appeared through this study that the total water needed for domestic use of the population of the study area was (2.486) million / m3 annually, in the year (2016). The amount of water required for agricultural crops and orchards is estimated at (36.109) million/m3 annually, and this is where the most is consumed compared to other uses in the area, The amount of water used by the livestock in the area is (146) million/liter annually, and the total water consumption of chicken fields and poultry birds is (7.16) million/liter annually. The estimated amount of water used in the food industry is (0.014) million m3/year. The amount of surface and ground water is estimated at (171.698) million/m3 in the study area, and surface water represents (65.45%), while groundwater represents (34.55%), and the amount that is consumed is estimated at (38.762) million/m3 for all uses, and it is clear from the above that there is a surplus of water, said surplus is estimated to be at (132.936) million/m3.